Effect of Peer Assessment Technique on Secondary School Students' Achievement, Interest and Study Habit in Chemistry - Samuel, Dr. Nkiru N.C.; Okonkwo Ifeoma G.A (Journal of Research in Industrial Technology and Educational Studies, 2025)
This study investigated the effect of peer assessment technique on secondary school students' achievement, interest, and study habits in chemistry in Anambra State, Nigeria. Using a quasi-experimental research design, 240 senior secondary school two (SS2) chemistry students from eight randomly selected schools were assigned to experimental and control groups. The experimental group utilized peer assessment techniques while the control group used conventional assessment methods. Three instruments were developed: Chemistry Achievement Test (CAT), Chemistry Interest Scale (CIS), and Chemistry Study Habit Inventory (CSHI). Data analysis employed mean, standard deviation, and Analysis of Covariance (ANCOVA). Results revealed that students exposed to peer assessment techniques significantly outperformed those taught using conventional technique in achievement (F=27.42, p
Keywords: Peer assessment; Chemistry education; Student achievement; Interest; Secondary education; Anambra State; Study habits